2009
DOI: 10.1371/journal.pone.0004512
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Prevent Intestinal Barrier Dysfunction in Acute Pancreatitis in Rats via Induction of Ileal Mucosal Glutathione Biosynthesis

Abstract: BackgroundDuring acute pancreatitis (AP), oxidative stress contributes to intestinal barrier failure. We studied actions of multispecies probiotics on barrier dysfunction and oxidative stress in experimental AP.Methodology/Principal FindingsFifty-three male Spraque-Dawley rats were randomly allocated into five groups: 1) controls, non-operated, 2) sham-operated, 3) AP, 4) AP and probiotics and 5) AP and placebo. AP was induced by intraductal glycodeoxycholate infusion and intravenous cerulein (6 h). Daily prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 48 publications
(84 reference statements)
4
69
1
6
Order By: Relevance
“…LR administration in the present study also enhanced the activities of SOD, CAT, and GPx in the liver and RBCs signifying improved free radical clearance system. Previous studies have shown that oral administration of lactobacilli and fermented milk whey promotes glutathione biosynthesis in tissues which could explain increased GPx activity in LR-fed groups (Zommara et al 1998;Lutgendorff et al 2009). The liver is the major site of glutathione synthesis and transport and thus could explain the apparent effects of LR consumption on GPx activity in liver and RBCs.…”
Section: Discussionmentioning
confidence: 98%
“…LR administration in the present study also enhanced the activities of SOD, CAT, and GPx in the liver and RBCs signifying improved free radical clearance system. Previous studies have shown that oral administration of lactobacilli and fermented milk whey promotes glutathione biosynthesis in tissues which could explain increased GPx activity in LR-fed groups (Zommara et al 1998;Lutgendorff et al 2009). The liver is the major site of glutathione synthesis and transport and thus could explain the apparent effects of LR consumption on GPx activity in liver and RBCs.…”
Section: Discussionmentioning
confidence: 98%
“…The reduction of GSH levels can hamper the ROS clearance, causing damage to cellular components (Lushchak, 2011). Several lactic acid bacteria were able to induce the biosynthesis of GSH in rat ileal mucosa or pancreas (Lutgendorff et al, 2009). Clear positive effects of probiotics have been often observed on immune or oxidative stress status when fish are subjected to stress situations.…”
Section: Discussionmentioning
confidence: 99%
“…The Cd-binding ability of CCFM8610 appears to be important for the inhibition of intestinal Cd absorption, because it enables CCFM8610 to sequester Cd before intestinal absorption and increase Cd excretion as Lactobacillus strains are excreted through feces (17). However, as a considerable number of studies have shown that oral administration of probiotics can prevent intestinal barrier dysfunction by modulating immune responses, inducing tight-junction maturation and inhibiting abnormal necrosis of epithelial cells (18)(19)(20)(21), further evidence is needed to establish whether probiotics, such as CCFM8610, can inhibit Cd absorption by protecting the intestinal barrier.…”
mentioning
confidence: 99%